The Analysis of Communication Strategies in Lady Gaga Talk Show - Ratna Kumalasari; Basuki Basuki; Zulia Chasanah (Scripta : English Department Journal, 2022)
The purpose of this study was to examine the different sorts of communication methods used in Lady Gaga's talk show and to discuss how these strategies are used in teaching speaking. The descriptive qualitative method was used in the study. The researcher conducts research on communication strategy theory, focusing on the Dornyei et al theory (1995). The information is gathered from the participant's discussions on the talk program. The researcher performed some steps when it came to data analysis. The first step is to download a video from YouTube. The second step is to download the transcription. Third, double-checking both the video and the transcription to ensure accuracy. Identifying the many types of communication methods used in Lady Gaga's talk show is the fourth step. The findings of this study revealed that there were 23 communication methods, including 1 avoidance strategies (4%), 2 achievement or compensatory strategies (9%), 17 stalling or time gaining strategies (74%), 2 self-monitoring strategies (9%), and 1 interactional strategies (4% ). Based on the results of each strategy, it can be stated that the majority of communication strategies involve stalling or time gaining . The researcher hopes that this thesis will contribute to the advancement of communication knowledge, particularly communication strategies for teachers, students, and other researchers involved in teaching speaking.